2022
DOI: 10.1093/cercor/bhac333
|View full text |Cite
|
Sign up to set email alerts
|

First-time fathers show longitudinal gray matter cortical volume reductions: evidence from two international samples

Abstract: Emerging evidence points to the transition to parenthood as a critical window for adult neural plasticity. Studying fathers offers a unique opportunity to explore how parenting experience can shape the human brain when pregnancy is not directly experienced. Yet very few studies have examined the neuroanatomic adaptations of men transitioning into fatherhood. The present study reports on an international collaboration between two laboratories, one in Spain and the other in California (United States), that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 126 publications
1
13
0
Order By: Relevance
“…These included both structural changes, as observed in increased gray matter volume in the hypothalamus, amygdala, striatum, and lateral prefrontal cortex and decreased gray matter volume in orbitofrontal cortex, posterior cingulate cortex, and insula during the first 4 months postpartum (P. Kim et al, 2014). Gray matter reduction has also been found in two cohorts of fathers imaged before or during pregnancy and after the birth of their first child (at 2 or 7-9 months) and pointed to decreases within the default mode and visual networks (Martínez-García et al, 2022).…”
Section: Newbornmentioning
confidence: 98%
“…These included both structural changes, as observed in increased gray matter volume in the hypothalamus, amygdala, striatum, and lateral prefrontal cortex and decreased gray matter volume in orbitofrontal cortex, posterior cingulate cortex, and insula during the first 4 months postpartum (P. Kim et al, 2014). Gray matter reduction has also been found in two cohorts of fathers imaged before or during pregnancy and after the birth of their first child (at 2 or 7-9 months) and pointed to decreases within the default mode and visual networks (Martínez-García et al, 2022).…”
Section: Newbornmentioning
confidence: 98%
“…Other research has found fatherhood status and number of children to be associated with gray matter thickness in multiple cortical regions as measured in older men; 43 prenatal‐to‐postpartum changes to the precuneus in first‐time fathers, 13 and both increases and decreases in subcortical and cortical regions among fathers followed over several months in the early postpartum period 44 . In a collaborative study that include part of the sample included in the current manuscript as well as an additional sample from Spain, men showed gray matter volume decreases in the cortex across the transition to parenthood but did not show significant subcortical change 26 . More research is needed to understand how the male brain changes across the transition to parenthood and the potential mechanisms of these changes, such as partner contact, parenting experience, energetic and hormonal shifts, or other possible explanations 5 .…”
Section: Discussionmentioning
confidence: 91%
“…Study data are available upon reasonable request. MRI data from about half of the fathers in the current sample ( n = 20) was included in another published manuscript, 26 which pooled these data with data from another sample of Spanish men and reported on gray matter volume change in the cortex. We have also reported on oxytocin data from these fathers in two published papers that are described in the introduction 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…To further elucidate whether a possible change in ToM is linked to pregnancy‐related neurobiological changes or parenting behavior in general, it would be interesting to examine whether a change in ToM ability also occurs in parents that do not undergo pregnancy. Although the pronounced changes in brain structure as observed in primiparous women across pregnancy have not been detected in parents who do not undergo pregnancy, 1 other studies have observed both increases and decreases in gray matter in a range of brain areas in fathers 44,45 . Additionally, higher prenatal testosterone in fathers was linked to greater activation in the brain during presentation of infant stimuli 46 .…”
Section: Discussionmentioning
confidence: 98%